Athletic performance and birth month: Is the Relative Age Effect more than just selection bias? - Sandercock, G. R. H.; Ogunleye, A. A.; Parry, D. A.; Cohen, D. D.; Taylor, M. J. D.; Voss, C. (International Journal of Sports Medicine, 2014)
The aim of this study was to determine if month of birth affects performance in 3 tests of physical function in children and adolescents. We measured cardiorespiratory fitness, handgrip strength and lower-body power expressed them relative to (whole year) age then compared scores between calendar year birth-months. We also expressed test performance as the likelihood of achieving criterion-referenced fitness standards. There were significant main effects of birth-month for cardiorespiratory fitness (F=4.54, p<0.001), strength (F=6.81, p<0.001) and power (F=3.67, p<0.001). Children born in November were fitter and more powerful than those born at other times, particularly the summer months (April, May and June). October-born children were stronger than those born in all months except September and November. This relationship was evident despite controlling for decimal age and despite no significant inter-month differences in anthropometric characteristics.